2017
DOI: 10.1097/mbc.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Novel microspheres reduce the formation of deep venous thrombosis and repair the vascular wall in a rat model

Abstract: L-Arginine (L-arg), widely known as a substrate for endogenous nitric oxide synthesis, can improve endothelial function associated with the vasculature, inhibit platelet aggregation, and alter the activity of vascular smooth muscle cells. P-selectin is a membrane component of the platelet alpha-granule and the endothelial cell-specific Wiebel–Palade body that plays a central role in mediating interactions between platelets and both leukocytes and the endothelium. The experiment was designed to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
1
0
0
4
Order By: Relevance
“…Our results indicated that the effect of cotinine on DVT in rats was due to activation of the TLR-4/NF-κB signaling pathway, which revealed the specific role of cotinine in DVT in rats. Our results are similar to those seen in previous studies, which provides evidence that cotinine aggravates inflammation through TLR-4/NF-κB [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that the effect of cotinine on DVT in rats was due to activation of the TLR-4/NF-κB signaling pathway, which revealed the specific role of cotinine in DVT in rats. Our results are similar to those seen in previous studies, which provides evidence that cotinine aggravates inflammation through TLR-4/NF-κB [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…Couture et al (2011) utilizando o FeCl3 a 10% por 3.5 minutos no vaso e retirada após 1 hora encontraram uma média de peso de 14.7±1.0mg. Dai et al (2017) utilizando o método somente com FeCl3 na VCI, na concentração de 10% e exposição por 5 minutos obtiveram peso seco (após 24 horas) médio de 6.10mg±3.60mg. São poucas as publicações contendo a área de oclusão como parâmetro avaliado em modelos animais de trombose.…”
Section: Discussionunclassified
“…Também tem sido utilizado em ratos um método de indução de trombose venosa associando ligadura parcial com lesão endotelial através do uso de FeCl3 (Gustafsson et al, 2001;Peternel et al, 2005;Hennan et al, 2008). Finalmente, Dai et al (2017) utilizaram exclusivamente o método de lesão endotelial com o FeCl3 para a indução de trombose venosa em ratos.…”
Section: Introductionunclassified
See 2 more Smart Citations